Male and Female Prostitutes: A Fact of Indonesia - Koentjoro Soeparno; Budi Andayani (Faculty of Psychology, Universitas Surabaya, 2014)
Prostitution had been being a sexy problem easy to talk about but difficult to be studied in depth because of personal, social, and professional risks a researcher should deal with. Prostitution as a field of study had many problems to be considered. The term prostitute it-self was debatable since there were many interests in the choice of using the label “prostitute”, “wanita tuna susila”, “commercial sex worker”, or “woman sex worker” and so on. Various definitions of prostitution in Indonesia indicated different perspectives in the society in per-ceiving prostitution. One perspective considered prostitution as crime, embarrassing the family, and a sin. Another emphasized that prostitutes were family heroes, family bread winners, and were not criminals. Prostitution had been being a beneficial business for every one involved, however, morality became a crucial matter never been considered. The major problem of morality in personal domain was the management of sexual desire. In a wider range, however, prostitution had been entangled with problems of family living and varied complex systems. Intervention to prostitution in Indonesia thus should be based on deep and correct under-standing. The conclusion and suggestions along with prostitution in Indonesia map could fulfil further understanding.